2020
DOI: 10.1093/intqhc/mzaa142
|View full text |Cite
|
Sign up to set email alerts
|

Chronic disease and medical spending of Chinese elderly in rural region

Abstract: Objective To determine whether or not chronic disease positively impacts medical costs among the rural elderly in China and to calculate medical expenditure induced by chronic disease between different groups of the rural elderly, as well as provide insight into the factors that affect medical losses induced by chronic disease among different household registration groups and different New Rural Pension Scheme statuses. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…According to the results of heterogeneity analysis, the chronic healthcare costs of urban seniors are higher than those of rural seniors, which is consistent with previous research ndings [12,48,49]. Due to the relatively lower income, rural elderly has a lower rate of healthcare service consumption.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to the results of heterogeneity analysis, the chronic healthcare costs of urban seniors are higher than those of rural seniors, which is consistent with previous research ndings [12,48,49]. Due to the relatively lower income, rural elderly has a lower rate of healthcare service consumption.…”
Section: Discussionsupporting
confidence: 88%
“…Referring to existing studies [12,19,20], we controlled for a number of variables that in uence the utilization and cost of healthcare services for the elderly in the model, including age, gender (male = 0, female = 1), residence (rural = 0, urban = 1), education level (primary and below = 0, middle and above = 1), marital status (other = 0, cohabited = 1), health insurance coverage (no = 0, yes = 1), smoking status (none = 1, quit = 2, still = 3), drinking status (none = 1, quit = 2, still = 3), body mass index (BMI) (underweight = 1, normal weight = 2, overweight = 3, obesity = 4), activities of daily living (ADL), annual household income per capita.…”
Section: Covariatesmentioning
confidence: 99%
“…A number of previous studies have documented the relationship between chronic disease and selfreported health and have consistently shown that chronic diseases have a negative impact on health [39][40][41]. Chronic diseases are a serious threat to the health of the elderly and are a common problem that needs to be addressed globally [42,43]. This study also provides scientific evidence for the promotion of the self-rated health among the MEFC.…”
Section: Association Between Morbidities and Self-rated Healthmentioning
confidence: 56%
“…Previous study demonstrated that among older Chinese adults (age ≥ 60 years), the overall prevalence of multimorbidity was up to 87.0% in urban residents [ 13 ], while the proportion was even up to 90% [ 14 ] in rural residents. The medical burden of chronic diseases has become the largest proportion of medical expenses of rural residents in China [ 15 ].…”
Section: Introductionmentioning
confidence: 99%